Japan’s Stock Market Performance: Evidence from Toda-Yamamoto and Dolado-Lutkepohl Tests for Multivariate Granger Causality - Guru-Gharana, Kishor K.; Rahman, Matiur; Islam, Anisul M. (International Journal of Economics and Financial Issues, 2021)
This paper empirically examines the causal linkages of Japan’s stock market (proxied by Nikkei 225 index) performance with selected key macroeconomic fundamentals. Relatively recent Toda-Yamamoto and Dolado-Lutkepohl, multivariate Granger causality tests are implemented. Monthly time series data from September 1974 to February 2017 with a large sample size of 510 monthly observations covering the floating exchange rate regime were utilized. The study documents some interesting and some unexpected results. Bi-directional causality is evidenced only between the stock market and the industrial production. Somewhat counterintuitively, unidirectional causality runs from stock market to money supply. Furthermore, unidirectional causality flows from interest rate (bond yield) to stock market. Not so surprisingly, no causality is detected between the stock market and the general price level. This is also true for stock market and exchange rate. The above findings may aid Japanese policy makers to formulate appropriate financial, monetary and exchange rate management policies. Japan should give second thought on the efficacy of its over reliance on monetary policy with interest-rates targeting and should prepare itself for launching a pragmatic fiscal stimulus program. Keywords: Stock Market; Macroeconomics Fundamentals; Granger Causality JEL Classifications: E44, F41, G15 DOI: https://doi.org/10.32479/ijefi.11262